Soil conditioning in EPB shield tunnelling – An overview of laboratory tests. Issue 5 (1st October 2019) - Peila, Daniele; Martinelli, Daniele; Todaro, Carmine; Luciani, Andrea
Abstract: The application of full‐face mechanized tunnelling, mainly with EPB shielded machines, has widely increased in the last years and today it can be considered the key technology when tunnelling in soils above and below the water table. The applicability range of EPB machines has widened thanks on one side to the technological and mechanical progresses and on the other side to the quality and effectiveness of the conditioning products. No recognized standards are available for laboratory testing of conditioned soil and each research centre has developed its own procedures and methods. In this paper, an overview of the most frequently used procedures is presented and discussed briefly.